The State of the Art in Computational Intelligence Proceedings of the European Symposium on Computational Intelligence held in Košice, Slovak Republic, August 30-September 1, 2000 - Sinčák, Peter; Vaščák, Ján; Kvasnička, Vladimír; Mesiar, Radko (Advances in Soft Computing, 2000)
Computational intelligence is a very dynamic domain of modern information society which integrates fields such as neural networks, fuzzy systems, evolutionary computation and intelligent systems in general. The book presents papers from the European Symposium on Computational Intelligence held in Kosice (Slovak Republic) in August 2000. It contains theoretical studies as well as a chapter on applications and case studies. One of the main results is the combination of various techniques into hybrid intelligent systems which will be very important for the development of intelligent information systems in the 21th centrury. With forewords written by L. Zadeh, D. Goldberg, and K. Fukushima